Late Motorisation and Sprawl Cities in Latin America: Defining its Limits, Hypothesising on its Future - Covarrubias V., Alex (Editorial Pontificia Universidad Javeriana, 2013)
The present paper defines the late motorisation of Latin America as its outdated arrival to mobility patterns and urban sprawl characterised by an increased utilisation of private vehicles. It states that the turning point took place the moment developing countries became main producers and consumers of private vehicles. Furthermore, it evidences its historic correspondence to a development model already obsolete in developed countries, of which the autopoietic mechanisms between cities, the oil interval and the propagation of private vehicles has been severely questioned. This paper intends to promote scholarly debate by making a contribution to the study of problems involving mobility and urbanisations set forth by Vasconcellos, specialists of the Corporación Andina de Fomento (CAF), Lizárraga and others. It offers a hypothetical reflective research, with a deductive-inductive design, qualitative techniques of participant observation and interviews with social, institutional and productive actors, carried out in Mexico, Brazil, Colombia and Argentina.